Juli Jelita - gulo, juli jelita; Dr., S.E., M.M., Suhardi (LPPM Universitas Putera Batam, 2022)
In business competition in the era of globalization, a company can have good Human Resources (HR) so that it can increase optimal output. Human resources are the most important part in the running of a company. The purpose of this study was to analyze the effect of Work Experience, Achievement, and Work Discipline partially and simultaneously on Job Promotion at PT JP Technology. The population in this study were all employess of PT JP Technology with using a saturated sampling is entire populations as a sample who founds 112 people. The data analysis technique in this study used multiple linear regression analysis, classical assumption test, and statistical test. The results showed, among others: (1) Work Experience partially positive and significant effect on Job Promotion; (2) Partial work performance has a positive and significant effect on Job Promotion; (3) Work Discipline partially has positive and significant effect on employee performance; (4) shows that work experience, work performance and work discipline simultaneously have a positive and significant effect on job promotion.